2019
DOI: 10.1016/j.seizure.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

A study of perfusion changes with Insula Epilepsy using SPECT

Abstract: The non-invasive localisation of insular lobe epilepsy is a challenge. We aimed to determine if ictal SPECT is a reliable adjunctive test in insular cases and to explore its role in the tailoring of intracranial strategies. Method: From a dataset of patients who underwent SEEG between December 2012 and December 2016, we collected patients with focal insular onset epilepsy. We examined semiology, EEG, PET and SPECT hyperperfusion pattern with SISCOM. We also reviewed relevant literature. Results: 5 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Propagation of insular seizures is typically from inside the insula to extrainsular connections [7]. The contralateral insula engagement could also be very fast in less than 1 s [16]. Here, we found that the posterior insular onset seizures spread both to extrainsular and intrainsular regions, while opercular onset seizures tend to propagate to extrainsular regions.…”
Section: Electrographic Findingsmentioning
confidence: 51%
“…Propagation of insular seizures is typically from inside the insula to extrainsular connections [7]. The contralateral insula engagement could also be very fast in less than 1 s [16]. Here, we found that the posterior insular onset seizures spread both to extrainsular and intrainsular regions, while opercular onset seizures tend to propagate to extrainsular regions.…”
Section: Electrographic Findingsmentioning
confidence: 51%
“…In this series, only two patients had insular abnormalities on MRI. SPECT is thought to be of moderate value in identifying insular epilepsy [ 20 , 21 ]. Similarly, PET has been thought to generate inconsistent findings, though some recent studies may suggest otherwise [ 20 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that focal seizures involving a CdG sign in the semiology does not always localize the SOZ to the frontal lobe. Finally, because of its depth relative to other regions of the brain, the insula cannot be reliably delineated by scalp EEG recordings [14]. Here, SEEG recorded electrographic seizure onset from contacts implanted into the anterior insula prior to involvement of the frontal lobe when the clinical semiology involving the CdG sign became evident.…”
Section: Discussionmentioning
confidence: 99%